Number 42 (July 2001) - Southern Fishes Council (Southeastern Fishes Council Proceedings, 2001)
(July 2001) - Longitudinal succession of fishes in the Dan River in Virginia and North Carolina (Blue Ridge/Piedmont Provinces). By Fred C. Rohde, Rudolf G. Arndt and Scott M. Smith Minutes, Business Meeting, 26th Annual Meeting, Southeastern Fishes Council Regional Southeastern Fishes Council Reports
Keywords: fishes; dan river; blue ridge; piedmont